The Effectiveness of Audiovisual-Based Health Education on Anxiety Levels Among Families of ICU Patients: an Analysis Using Roy’s Adaptation Model - Anis Windari; Fery Agusman; Anny Rosiana M (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT The Intensive Care Unit (ICU) is a hospital unit equipped with specialized staff and medical equipment to care for patients in critical and life-threatening conditions. This situation often causes family members of ICU patients to experience stress, fear, and anxiety regarding the patient’s condition. Anxiety experienced by ICU patients’ families can have both physical and psychological impacts. Interventions are needed to help families adapt and manage this anxiety, one of which is audiovisual-based health education. This study to determine the effectiveness of audiovisual-based health education in reducing anxiety among families of ICU patients using Roy’s Adaptation Model.This study was quasi-experimental with a two-group pretest-posttest control group approach. The research was conducted from December 2024 to January 2025 at RSUD dr. Loekmono Hadi Kudus. The population consisted of 65 family members of patients admitted to the ICU. Using purposive sampling, 55 respondents were selected, divided into an intervention group (28 respondents) and a control group (27 respondents). The intervention used audiovisual media in the form of a video accessed through smartphones. The instruments included video, smartphone (belonging to the family), and the Hospital Anxiety and Depression Scale (HADS) questionnaire. Data were analyzed using an independent sample t-test. This study has obtained an Ethical Clearance Certificate with number 69/KEPK/RSLH/VIII/2024. The independent sample t-test analysis showed a p-value of 0.017 (p 0.05). Audiovisual-based health education is effective in reducing anxiety among families of ICU patients using Roy’s Adaptation Model. It is recommended that hospitals provide audiovisual-based health education as part of a family support program in the ICU. Keywords: Anxiety, Audiovisual, Family, ICU, Roy’s Adaptation Model.